Process improvement of biogas production from anaerobic co-digestion of cow dung and corn husk - Avicenna, Avicenna; Mel, Maizirwan; Ihsan, Sany Izan; Hendroko Setyobudi, Roy (Elsevier, 2015)
A study of organic loading rate (OLR) and effect of NaOH concentration on the pretreatment stage of corn husk (CH) was conducted by Face-Centered Central Composite Design (CCF) to improve the biogas production. Three levels of OLR at 25.0 g VS · L–1 · d–1 (OLR25), 35.0 g VS · L–1 · d–1 (OLR35), and 45.0 g VS · L–1 · d–1 (OLR45) were performed with NaOH pretreatmentconcentration of CH at 25.0 % (N25), 35.0 % (N35), and 45.0 % (N45) (w/w). The optimum production of biogas at 67.6mL · min–1 with methane concentration of 63.4 % has been obtained at the application of OLR at 43.6 g VS · L–1 · d–1 andNaOH concentration at 33 % (w/w).